Proceedings of the Second Regional Groundnut Workshop for Southern Africa: 10-14 February, 1986 - Bock, K.R.; Cole, Desiree L.; Wightman, J.A.; Nigam, S.N.; Mertin, J.V. (Patancheru, Andhra Pradesh 502 324, India: International Crops Research Institute for the Semi-Arid Tropics(ICRISAT), 1987)
The opinions in this publication are those of the authors and not necessarily those of ICRISAT. The designations employed and the presentation of the material in this publication do not imply the expression of any opinion whatsoever on the part of ICRISAT concerning the legal status of any country, territory,city, or area,or of its authorities, or concerning the delimitation of its frontiers or boundaries. Where trade names are used this does not constitute endorsement of or discrimination against any product by the Institute.
Sponsored by- International Development Research Centre (IDRC) and ICRISAT.
Keywords: Groundnut Workshop; Crops Research Institute; Southern Africa; Harare; Zimbabwe; Patancheru; Andhra Pradesh; India